PROGRESSIVE TECHNOLOGIES IN THE DESIGN OF OUTERWEAR REFLECTING ELEMENTS - Mežinska, Silvija; Salmane, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The purpose of this article is to substantiate the use of advanced technologies as a processing method of modern, versatile designing resources and environmentally friendly textiles, and to demonstrate their use in the design of light-reflective material elements in outerwear collections. Functional decorative solutions, using reflective materials, are topical in contemporary fashion design for the dark time of the day and can be realized using modern technology. Research methods: theoretical - literature; empirical - experiment and data processing. Period - 2018/2019. study year. The study is of practical importance as it demonstrates the impact of technological parameters on textiles. The availability of laser processing and 3D equipment at the Rezekne Academy of Technology provides opportunity for experimental work on different thickness, different fiber fabrics with a carbon dioxide laser system and different filaments for 3D printing, determining the optimum processing parameters for a particular type of cloth. As a result, the design of the collection is developed, providing the decorative and functional significance of the garments with reflective elements.